Institutional and major persistence among first-generation engineering students in a first-year program: a grounded theory study - Hoffman, David Fredrick (Kansas State University, 2020)
This research study examined the factors that positively influenced the first-to-second year institutional and major persistence efforts of first-generation engineering undergraduates that participated in a first-year program at Kansas State University, a large, land-grant, public, and four-year institution in the Midwestern United States. Historically, both first-generation college students and engineering majors have lower rates of persistence when compared to other populations. In order to provide sufficient context for the study, previous work on college student retention, engineering major persistence, first-year program participation, and the experience of first-generation undergraduate students was examined. Through these efforts, it was determined that the first-year persistence of first-generation engineering students that had participated in a first-year program had not been sufficiently examined. The purpose of this study was to explore the factors that positively influenced the institutional and major persistence efforts of first-generation engineering undergraduate students in a first-year program through a qualitative design and a grounded theory methodology. The following research question at the center of the study was addressed: What were the factors that positively influenced the first-to-second year institutional and major persistence efforts of first-generation engineering students that participated in a first-year program? Through the incorporation of a grounded theory methodology, first-generation engineering students that participated in first-year program and had persisted in engineering from their first to their second year were interviewed. Within the interview setting, the research participants provided considerable insight into their experiences and persistence efforts throughout their first year in the engineering program. The collection and analysis of data led to findings that suggest the existence of six primary elements that positively influenced the first-to-second year institutional and major persistence of first-generation engineering students. By adhering to the grounded theory methodology, a theoretical model, which can be identified as the First-Generation Engineering Student First-Year Persistence Model, was developed. The First-Generation Engineering Student First-Year Persistence Model illustrates the six primary elements that positively influenced the first-to-second year institutional and major persistence for first-generation engineering students and the various subcategories of factors that contribute to each element. Furthermore, a summary of and further discussion of the primary findings were provided. Finally, recommendations for future studies concerning first-generation engineering students and first-to-second year institutional and major persistence efforts were offered.
Keywords: Persistence; Engineering; First-generation; Grounded; Qualitative